2023
DOI: 10.1017/s0007114523000028
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of non-alcoholic fatty liver disease and its association with lifestyle habits in adults in Chile: a cross-sectional study from the National Health Survey 2016–2017

Abstract: Non-alcoholic fatty liver disease (NAFLD) represents an excessive fat accumulation within the liver, usually associated with excess body weight. A liver biopsy is the gold standard for diagnosis, but it is inapplicable in population-based studies. In large populations, non-invasive methods could be used, which may also serve to identify potential protective factors. We aimed to: [a] estimate NAFLD prevalence in the adult population in Chile by using non-invasive methods; and [b] determine the association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…A case-control study revealed that a stronger commitment to a healthy lifestyle, as indicated by a higher score in healthy lifestyle factors, was linked to a reduced risk of NAFLD [43]. According to the 2016-2017 Chilean National Health Survey, a reduced prevalence of smoking, increased engagement in moderate-vigorous physical activity, and higher consumption of whole-grains were linked to a decreased likelihood of developing NAFLD [23]. Furthermore, the consumption of alcohol, even in moderate amounts, has been linked to worsened liver conditions [11,12].…”
Section: The Correlation Between the Severity Of Fatty Liver And Life...mentioning
confidence: 99%
See 2 more Smart Citations
“…A case-control study revealed that a stronger commitment to a healthy lifestyle, as indicated by a higher score in healthy lifestyle factors, was linked to a reduced risk of NAFLD [43]. According to the 2016-2017 Chilean National Health Survey, a reduced prevalence of smoking, increased engagement in moderate-vigorous physical activity, and higher consumption of whole-grains were linked to a decreased likelihood of developing NAFLD [23]. Furthermore, the consumption of alcohol, even in moderate amounts, has been linked to worsened liver conditions [11,12].…”
Section: The Correlation Between the Severity Of Fatty Liver And Life...mentioning
confidence: 99%
“…The current studies mainly concentrate on the general public or particular groups of patients [21][22][23]. Furthermore, the majority of studies investigate the demographic and clinical traits of individuals who have or do not have fatty liver [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El exceso de peso es uno de los factores de riesgo más relevantes para el desarrollo de HGNA. La prevalencia de HGNA aumenta progresivamente desde personas con peso normal hasta personas con obesidad mórbida 3 .…”
Section: Estimado Editorunclassified
“…Para ello usamos dos índices no invasivos llamados FLI 6 y LAP 7 (del inglés Fatty Liver Index y Lipid Accumulation Product, respectivamente). Encontramos que la prevalencia de HGNA es 39,4% [IC95% 36,2-42,8] con el índice FLI, y 27,2% [IC95% 24,2-30,4] con el índice LAP 3 .…”
Section: Estimado Editorunclassified